(3GdfgGjIs - (3GdWhSj, CHh LYaQ, eMeO Hf GdMSf Hf Ydj, J (B460(3g`s ((3YRjR Hf egOj GdfhNGdg Jhdjes)
(3ChdgG (B:s
(3GdMeO ddg eSJMb GdMeO (B.. (3HGH eGgjI GdWgGQI hcjajI JQJjHgG , GdWgGQI aj GdTQjYI GSe deG jSJHGM Hg GdONhd aj GdUdGI hgj JfbSe bSejf hVhA hJjee heOGQgG Ydi CQHYI CTjGA CMOgG hLhH GdWgGQI (B...s
(3BNQgG (B:s
.. (3hef CJda Ydi eSde TjFG ef GdedGgj GdJj dG jLhR JedcgG eKd GdYhO hGdWfGHjQ heG CTHg Pdc de jcf Ydjg TjA aEf CJda Pdc Ydi Pej aj MQRg cGf Ydjg VeGfg (B...(3Je GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\84s
(3GdPQjYI (B24\2141s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis